Türkmenistan'ın Azerbaycan ve Türkiye ile ilişkileri (1991-2020) - Esen, Erdal Onur (My University, 2022)
Sovyet Sosyalist Cumhuriyetler Birliği dağılma sürecine girdiğinde bağımsızlığını ilan eden cumhuriyetlerden biri de Türkmenistan'dır. Türkmenistan bölge ülkelerine göre nüfusu az, toprakları çöllerle kaplı ama doğalgaz zengini bir ülkedir. Ülkenin kurucu Cumhurbaşkanı Saparmurat Niyazov ekonomik olarak kötü durumda ve yetişmiş insan gücünden mahrum olan ülkesinin büyük güçlerin etkisi altına girmesini engellemiş, Türkmen doğalgazını dünya pazarına sunmak için çeşitli yollar aramıştır. Niyazov ülkesini ayakta tutmayı başarmış olsa da özellikle dış politikadaki tercihleri ülkesinin yalnızlaşmasına sebep olmuştur. Kurbankulu Berdimuhammedov ile birlikte Türkmenistan için yeni bir dönem başlamıştır. Berdimuhammedov döneminde komşularla ilişkiler düzelmiş, dış politikada önceki döneme göre daha istikrarlı bir görüntü çizilmiştir. Yine onun döneminde ülkenin kaderini ilgilendiren en önemli konulardan bir olan Hazar Denizi'nin statüsü sorunu çözülmüştür. Türkmenistan'ın siyaset, ekonomi ve kültürel alanlarda en çok etkileşim içinde olduğu devletlerden ikisi Türkiye ve Azerbaycan olmuştur. İyi başlayan Türkmenistan-Türkiye ilişkileri Niyazov'un son yıllarında kopma noktasına gelmişse de Berdimuhammedov döneminde yıllar içerisinde iyi bir noktaya ulaşmıştır. Türkmenistan-Azerbaycan ilişkileri 2018'de Hazar Denizi'nin statüsü sorunu çözülene kadar yüksek gerilimli olmuştur. 2018 sonrasında ise iki ülke arasındaki ilişkiler daha olumlu seyretmektedir.

When the Union of Soviet Socialist Republics entered the process of disintegration, Turkmenistan became one of the republics that declared its independence. Turkmenistan was a country with a low population compared to the countries in the region, its territory was covered with deserts, but it was a country rich in natural gas. The founding president of the country, Saparmurat Niyazov, prevented his country, which was in a poor economic situation and deprived of trained manpower, from falling under the domination of the great powers, and sought various ways to deliver Turkmen natural gas to the world market. Although Niyazov managed to keep his country afloat, his preferences, especially in foreign policy, led to the isolation of his country. A new page has been opened for Turkmenistan with the Kurbankulu Berdimuhammedov era. During the period of Berdimuhammedov, relations with neighbors improved, and a more stable image was drawn in foreign policy than in the previous period. Moreover, during his period, the issue of the status of the Caspian Sea, which is one of the most important issues related to the fate of the country, was resolved. Two of the states with which Turkmenistan interacts the most in the political, economic and cultural fields have been Turkey and Azerbaijan. Although Turkmenistan-Turkey relations, which started well, came to a breaking point in the last years of Niyazov, they reached a good point in the period of Berdimuhammedov. Turkmenistan-Azerbaijan relations had been of high tension until the issue of the status of the Caspian Sea was resolved in 2018. After 2018, relations between the two countries are decisively improving.
Keywords: Azerbaijan; Azerbaycan; Berdimuhamedow; Berdimuhammedov; Caspian Sea; Dış ilişkiler; Foreign relations; Hazar Denizi; Niyazov; SSCB; Turkey; Turkmenistan; Türkiye; Türkmenistan; USSR